Beyond Ritual: Socio-Cultural and Economic Significance of the Sipulung Tradition in the Towani Tolotang Indigenous Community - Amin, Nurul Auliya; Pulubuhu, Dwia Aries Tina; Muhammad, Rahmat; Kasnawi, M. Tahir; Sakaria, Sakaria; Yahya, Yahya (SIGn Journal of Social Science, 2025)
The existence of local belief adherent groups in Indonesia continues to face challenges of marginalization and modernization. Amidst this vulnerability, the Towani Tolotang indigenous community in Sidenreng Rappang Regency demonstrates strong cultural resilience through the execution of the Sipulung tradition. This study aims to explore and analyze in depth the socio-cultural and economic significance of this communal tradition, which is proven to transcend mere dogmatic worship rituals. This study employed a qualitative, reflexive ethnographic approach. Primary data were collected through participant observation, in-depth interviews, and field notes at the Perrinyameng ancestral tomb site. The data were subsequently validated through source and methodological triangulation. The results show that the Sipulung tradition operates as a structural ecosystem that supports the community’s life sustainability through five main dimensions. First, the spiritual dimension manifests absolute obedience to Dewata Seuwae through the contemplative practice of Molalaleng guarded by the Uwatta figure. Second, the cultural education dimension transmits ancestral values through the habituation of early childhood. Third, the social dimension strengthens mechanical cohesion by regathering the Passompe within an inclusive space. Fourth, the economic dimension deconstructs the idea that ritual expenditure constitutes symbolic capital accumulation driven by the Resopa na temmangingngi hard-work ethos. Fifth, the entertainment dimension through the Massempe’ sport functions as a cultural catharsis. In conclusion, Sipulung is not merely a pilgrimage rite but a resolution instrument guaranteeing minority existence. These findings recommend the need for local government policy intervention to protect civil rights. Furthermore, the establishment of spatial protection for the Perrinyameng area is highly required as a bastion of indigenous community resilience.